Modified fiber fabric and preparation method thereof
By modifying cellulose fibers and using ammonia ammonium ammonium ammonium, the problem of sodium ion residue in carboxymethylcellulose ammonium water-absorbing materials is solved, and its water absorption and biocompatibility are improved, thus achieving its in many fields. Widely used.
Patent Information
- Application Number
- CN202411375314.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-29
AI Technical Summary
The existing carboxymethylcellulose ammonium water-absorbing materials have unbound non-volatile sodium ions and potassium ions residues during the preparation process, which affects their biocompatibility and water-absorbing properties, and is difficult to widely use in sanitary care, medical and other fields.
By modifying the cellulose fibers, using ammonia ammonization and undergoing strict acidification reactions, unbound sodium and potassium ions are removed, the water absorption and biodegradability of carboxymethylcellulose ammonium are improved, and high-efficiency is prepared water-absorbing material.
It has achieved efficient preparation of carboxymethylcellulose ammonium water-absorbing materials, with excellent water absorption, water retention and biocompatibility, and is suitable for sanitary care, medical care, industry, agriculture and forestry and other fields.
Smart Images

Figure BDA0005068537830000141 
Figure BDA0005068537830000151 
Figure HDA0005068537850000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cellulose, in particular to a modified fiber fabric and a preparation method thereof. Background Art
[0002] The water-absorbing materials on the market include ordinary water-absorbing materials and polymer water-absorbing materials. Ordinary water-absorbing materials such as paper and cotton fabrics are difficult to be widely used due to their limited water absorption capacity. Relatively speaking, polymer water-absorbing materials are more widely used in health care, medical treatment, industry, agriculture and forestry. Among them, the water-absorbing pad made of super absorbent resin has excellent water absorption and water retention, but due to the poor biodegradability of polypropylene super absorbent resin, it is easy to cause groundwater and soil environmental pollution. For this reason, people began to study environmentally friendly water-absorbing materials.
[0003] Cellulose is a long-chain natural polymer in which D-glucose monomers are dehydrated and connected in the form of β-1,4-glucosidic bonds, in which the hydroxyl group at the C6 position is a primary alcohol hydroxyl group, while the hydroxyl groups at C2 and C3 are secondary alcohol hydroxyl groups. The water-absorbing material prepared with cellulose as raw material has good degradability and biocompatibility. It uses the hydroxyl H on cellulose C2, C3, and C6 to be replaced by carboxymethyl groups, first making a CMC-H transition material with relatively low water absorption, and then alkalizing to obtain the corresponding water-absorbing material. The existing CMC-H material is made by papermaking or non-woven, and sodium ions or potassium ions are bound to CMC-H by adding sodium hydroxide, sodium carbonate, potassium hydroxide, etc. The unreacted sodium hydroxide, sodium carbonate, and potassium hydroxide will remain on the water-absorbing material, affecting the biocompatibility of the water-absorbing material, and it is difficult to be well applied in the fields of health care, medical treatment, etc.
[0004] Ammonium carboxymethyl cellulose is another derivative material prepared from cellulose. Existing methods for preparing ammonium carboxymethyl cellulose, such as a method for preparing ammonium carboxymethyl cellulose disclosed in patent application number CN201110457650.5 and a method for preparing high-viscosity ammonium carboxymethyl cellulose disclosed in patent application number CN202011249366.4, are all in powder form, usually used as a special purpose adhesive, mainly used for high-quality SCR denitration catalysts. In addition, fiber water absorption depends not only on the fiber material itself, but also on the "capillary phenomenon" between the fibers, that is, after the gaps between the fibers come into contact with water, the water will move along the fiber gaps due to the capillary phenomenon, and part of the water will fill the gaps between the fibers, while the water absorption characteristics of the "capillary phenomenon" of powdered ammonium carboxymethyl cellulose are relatively small. Therefore, in the prior art, ammonium carboxymethyl cellulose is difficult to be used as a cellulose water-absorbing material. Summary of the invention
[0005] The present invention aims at the shortcomings and deficiencies in the prior art and provides a reaction design which is ingenious, and can maintain the smooth progress of the reaction while eliminating the problem of residual unbound non-volatile sodium ions and potassium ions, thereby improving the preparation efficiency and product purity of the ammonium carboxymethyl cellulose water-absorbing material. The obtained ammonium carboxymethyl cellulose water-absorbing material has excellent water absorption, water retention, biodegradability and biocompatibility, and can be well applied to the modified fiber fabric in the fields of health care, medical treatment, industry, agriculture and forestry, and the preparation method and application thereof.
[0006] To achieve the above objectives, the present invention is implemented by the following technical scheme: the modified fiber fabric provided by the present invention, the fiber fabric raw material is based on maintaining the fiber shape, and is sequentially modified to carboxymethyl cellulose and ammoniumized with ammonia to obtain a fiber fabric of carboxymethyl cellulose ammonium;
[0007] The fiber fabric raw material undergoes a modification reaction to maintain its fiber shape. Specifically, during the modification reaction, in the fiber molecules of the fiber fabric raw material, the 1,4-glycosidic bonds (i.e., the connection between C1 and C4) in the glucose molecules connecting to form parallel cellulose chains remain unchanged, and modification reactions are performed on specific chemical groups occupying specific carbon positions C6, C2, and C3 on the molecular chains of the fibers.
[0008] Preferably, the degree of substitution in the fiber fabric of ammonium carboxymethyl cellulose treated with ammonia is 0.2-3.0, the terminal modification groups of the specific chemical groups at carbon positions C6, C2, and C3 in the ammonium carboxymethyl cellulose molecules include -CH2COONH4, the content range of which is limited to 4.3%-58.9%, and -CH2COONH4 is directly connected to the glucose unit of the fiber, and the breaking strength of the fiber in the fiber fabric of ammonium carboxymethyl cellulose is not less than 60% of the breaking strength of the fiber in the fiber fabric raw material.
[0009] Preferably, the cellulose fiber is natural cellulose fiber and / or regenerated cellulose fiber; the length of the cellulose fiber is not less than 0.5 mm. The cellulose fiber can be natural cellulose fiber such as cotton, hemp, bamboo, straw, etc., or regenerated cellulose fiber such as viscose, tencel, cuprammonium, modal, etc., or a mixed fiber of the above two types of fibers, which has a wide range of applications, abundant raw material sources, and good market prospects.
[0010] Preferably, in the process of modification to carboxymethyl cellulose, alkalization and etherification are carried out in sequence based on maintaining the fibrous shape of the cellulose fibers, and then an acid solution is added and mixed evenly, and the volume percentage concentration of the acid in the acid solution is ≥29%, and the modified product obtained after the acidification reaction is carboxymethyl cellulose CMC-H.
[0011] The preparation method of the modified fiber fabric is as follows: the fiber fabric raw material is modified to carboxymethyl cellulose and then ammoniumized with ammonia gas to obtain the fiber fabric whose modified product is ammonium carboxymethyl cellulose;
[0012] The fiber fabric raw material undergoes a modification reaction to maintain its fiber shape. Specifically, during the modification reaction, in the fiber molecules of the fiber fabric raw material, the 1,4-glycosidic bonds (i.e., the connection between C1 and C4) in the glucose molecules connecting to form parallel cellulose chains remain unchanged, and modification reactions are performed on specific chemical groups occupying specific carbon positions C6, C2, and C3 on the molecular chains of the fibers.
[0013] Preferably, the fiber fabric raw material is cellulose fiber, and the length of the cellulose fiber is not less than 0.5 mm;
[0014] In the process of modification to carboxymethyl cellulose, alkalization and etherification are carried out in sequence based on maintaining the fiber shape, and then acid solution is added and mixed evenly; the volume percentage concentration of the acid in the acid solution is ≥29%, and the modified product obtained after the acidification reaction is carboxymethyl cellulose CMC-H;
[0015] After washing, washed fibers are obtained;
[0016] The washed fiber is then treated with ammonia gas to obtain a fiber fabric whose modified product is ammonium carboxymethyl cellulose.
[0017] The fiber fabric of ammonium carboxymethyl cellulose is treated with ammonia gas to have a substitution degree of 0.2-3.0, the terminal modification groups of the specific chemical groups at the carbon positions C6, C2 and C3 in the ammonium carboxymethyl cellulose molecule include -CH2COONH4, and the content range of -CH2COONH4 is limited to 4.3%-58.9%, and -CH2COONH4 is directly connected to the glucose unit of the fiber, and the breaking strength of the fiber in the fiber fabric of ammonium carboxymethyl cellulose is not less than 60% of the breaking strength of the fiber in the fiber fabric raw material.
[0018] Preferably, the washed fiber is obtained after washing with water until the pH of the washing residue is ≥4.0.
[0019] Preferably, the post-treatment drying step in the ammoniation treatment step with ammonia is heating and drying, the fiber fabric after the ammoniation is heated and dried, the heat obtained is used to simultaneously remove the uncombined ammonia in the reaction, and the fiber fabric is heated and dried until the moisture content of the carboxymethyl cellulose ammonium fiber fabric is ≤15%. The drying at this time is to gradually control the moisture content to ≤15%, which can reduce the deformation of the fiber due to excessive water loss in a short period of time to a certain extent, thereby obtaining a carboxymethyl cellulose ammonium water-absorbing material with better mechanical strength.
[0020] Preferably, in the step of ammoniation with ammonia, the sheeting is first performed and then the ammoniation step is performed. This method of making cloth is more operable, more processes are applicable to sheeting, relatively speaking, there are fewer drying steps, and the production efficiency is higher. Specifically:
[0021] The washed fibers are firstly made into a primary sheet by a papermaking or non-woven process, and then the primary sheet is ammonized with ammonia gas to obtain an ammonized fiber sheet.
[0022] Preferably, in the process of preparing the washed fiber into a primary sheet,
[0023] When papermaking is adopted, in the papermaking step, the washed fiber is firstly put into pure water or ordinary fiber-water dispersion liquid and dispersed evenly, and then papermaking is carried out, and the weight ratio of the washed fiber to the ordinary fiber is 10-100:90-0; in the papermaking step, the total addition amount of the washed fiber and the ordinary fiber is 0.3-1.5wt% for papermaking, and the thickness of the single layer of papermaking is 7-30g / m 2 If the fiber content is too little and the thickness is too small, the breakage rate of the primary sheet obtained is high; if the fiber content is too much and the thickness is too large, the subsequent drying efficiency and effect of the primary sheet will be affected. Therefore, when the preparation method of the present invention uses the above papermaking parameters, the product performance is optimal.
[0024] When the non-woven process is used for sheet production, in the non-woven step, the washed fiber is first mixed with the ordinary fiber, and then the non-woven sheet is made, and the weight ratio of the washed fiber to the ordinary fiber is 10-100:90-0. In the non-woven step, the washed fiber and the ordinary fiber are reinforced into a non-woven fabric by mechanical, thermal bonding or chemical methods, and the gram weight is 9-600g / m 2 The nonwoven process can choose a variety of processing methods, such as hot rolling, spunlace, needle punching, etc. The hot rolling process has a lower gram weight, and the needle punching process has a higher gram weight. Therefore, the gram weight of the present invention can be adjusted between 9-600g / m according to different process requirements. 2 within the range of adjustment.
[0025] The papermaking in the sheet making of the present invention is to disperse the washed fibers evenly before papermaking; the non-woven is to orient or randomly arrange the washed fibers to form a fiber mesh structure, and then reinforce it by mechanical, thermal bonding or chemical methods. Preferably, the common fiber is one or more of bamboo fiber, cotton fiber, wood fiber, hemp fiber, regenerated cellulose fiber, polylactic acid fiber, polyvinyl alcohol fiber, polyethylene fiber, polyamide fiber, polyester, acrylic, polypropylene and ES fiber. The washed fibers of the present invention can be used to prepare pure carboxymethyl cellulose ammonium fiber sheets as needed, and can also be combined with other common fibers to make composite fiber sheets. Among them, the pure carboxymethyl cellulose ammonium fiber sheets have better water absorption and water retention; and the composite fiber sheets have better physical properties due to the incorporation of other common celluloses. By adding ordinary fibers, the physical properties and processability are enhanced. Natural cellulose can provide support for washed fibers. The cutting length of regenerated cellulose fibers can be increased as needed before processing to increase the tensile properties of the absorbent material. The added polylactic acid fibers, polyvinyl alcohol fibers, polyethylene fibers, polyamide fibers, polyester, acrylic, polypropylene and ES fibers are all thermoplastic, expanding the types of non-woven processes.
[0026] Preferably, in the step of ammoniation with ammonia, the ammoniation is first performed and then the tableting step is performed, specifically:
[0027] The washed fiber is first dried preliminarily, and then treated with ammonia to form CMC-NH4 fiber. The unbound ammonia is then removed by heating the air duct. The obtained fiber dry material is evenly spread and needle-punched to obtain an ammonium fiber sheet.
[0028] Preferably, the acid is a biocompatible acid, specifically one or more of acetic acid, citric acid, hydrochloric acid, nitric acid, and formic acid.
[0029] Preferably, the acidification is performed multiple times until the fiber acidification reaction is sufficient, and the total acidification time is 0.8h-1.5h. Through multiple acidification operations, it can be further ensured that the fiber as a whole is effectively and fully acidified in high-concentration acid, thereby ensuring sufficient acidification reaction.
[0030] Preferably, the acid solution also contains alcohol with a volume percentage concentration of 0-50%; the alcohol is one or more of methanol, ethanol, and isopropanol. In the step of preparing CMC-H, when the acid concentration is low, the water contained will have a certain swelling and solubility on the CMC-Na that is not fully acidified, and it is difficult to maintain the fiber morphology well. Combined with the characteristics of "fiber is difficult to dissolve in alcohol, and the fiber morphology can be maintained", the present invention can play a good role in inhibiting fiber swelling and dissolution by adding an appropriate amount of alcohol, so as to better keep the cellulose in fiber morphology. If the acid concentration is high in the step of preparing CMC-H, the degree of swelling and dissolution of the fiber is low at this time, and the addition of alcohol can be omitted. Methanol, ethanol and isopropanol are all common low-boiling alcohols, which have good miscibility with water, have little interference with cellulose, and are also convenient for subsequent impurity removal.
[0031] Preferably, ammonia is obtained by evaporating liquid ammonia, ammonia water or ammonia-alcohol water at a temperature of 0-130°C and a pressure of 102kPa to a pressure lower than the liquefied vapor pressure of ammonia at the corresponding temperature. The above liquid ammonia, ammonia water or ammonia-alcohol water all volatilize to generate ammonia at a set temperature and pressure; when the pressure is lower than 102kPa, the pressure is slightly lower than the basic atmospheric pressure, and even if the ammonium container is emptied of air, it is difficult to evenly touch the initial fiber when ammonia is filled, resulting in uneven reaction; the upper limit of the pressure is lower than the liquefied vapor pressure of ammonia at the corresponding temperature, because after the ammonia is liquefied, the fiber will directly dissolve into the liquid, it is difficult to maintain the fiber shape, and the subsequent product will become hard. On the other hand, when the temperature is lower than 0°C, the permeability of ammonia is poor and it is difficult to combine; the temperature is greater than 130°C, which is basically close to the carbonization temperature of cellulose, which easily leads to a decrease in fiber strength.
[0032] The water-absorbing material can be well applied to the fields of health care, medical treatment, industry, agriculture and forestry, and the application of the modified fiber fabric, the modified fiber fabric prepared by the above method has good water absorption, and at the same time has good biodegradability and biocompatibility, and can be widely applied to the fields of health care, medical treatment, industry, agriculture and forestry.
[0033] The present invention provides a modified fiber fabric and a preparation method thereof, which has the following beneficial effects:
[0034] (1) The modified fiber fabric and preparation method thereof of the present invention use cellulose fiber as raw material, and the fiber is kept in the modified state during the whole process. At the same time, the sodium ion removal rate of sodium carboxymethyl cellulose is fully considered, and the acid concentration is strictly controlled during the acidification process. Ammonia is used for ammoniation at a suitable temperature and pressure, and then the fiber is dried and the unbound ammonia is removed. The synergistic effect is cleverly designed to ultimately ensure the softness and physical properties of the product paper or nonwoven fabric.
[0035] The present invention can effectively restore the excellent water absorption and water retention of the fiber while ensuring the smooth progress of the reaction; in the subsequent drying process, on the one hand, the excess ammonia water can be directly volatilized, and on the other hand, the ammonia water can take away part of the water while volatilizing, which can effectively and quickly dehydrate and improve the drying efficiency. In addition, the biodegradability of the raw materials is relatively high, and no sodium ions are added to the system, so the obtained carboxymethyl cellulose ammonium water-absorbing material has both excellent biodegradability and biocompatibility.
[0036] Compared with the method for preparing sodium carboxymethyl cellulose fiber in the prior art, the method for preparing the modified fiber fabric of the present invention can save the residue of unbound non-volatile sodium ions and potassium ions while maintaining the smooth progress of the reaction, thereby significantly improving the preparation efficiency and product purity of the ammonium carboxymethyl cellulose water-absorbing material. The obtained ammonium carboxymethyl cellulose water-absorbing material has excellent water absorption, water retention and biodegradability, and can be well applied to the fields of industry, agriculture and forestry.
[0037] (2) The modified fiber fabric of the present invention has a wide range of applications, abundant raw material sources, and good market prospects.
[0038] (3) The preparation method of the modified fiber fabric of the present invention is to use the technology of "sheeting-ammoniation with ammonia-drying" or "drying-ammoniation with ammonia-needle punching-drying" to compare the use of alkali metal sodium hydroxide and potassium hydroxide. Sodium hydroxide and potassium hydroxide are prepared into water / alcohol solutions, which will dissolve the washed fibers after drying, making it difficult to make them into sheets.
[0039] If the CMC-H fiber is first made into a primary sheet and immersed in the solution to generate CMC-Na or CMC-K, although the obtained material can also achieve the purpose of high water absorption after drying, the Na and K that are not bound to the cellulose-COOH will remain on the fiber, causing the fiber to become hard or the biocompatibility to decrease. The present invention uses volatile NH3 as the cation that binds to -COOH. Although NH3 that is not generated into CMC-NH4 will also remain on the fiber, it can be removed during drying due to the volatility of NH3, so that the product water-absorbing material has good biocompatibility and can be better used in the fields of health care, medical treatment, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is a photo of the fiber fabric (cloth) of modified ammonium carboxymethyl cellulose prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0042] Fiber raw material (cellulose fiber): In the present invention, both natural cellulose fiber and regenerated cellulose fiber can be used. The present application selects commercially available products of bamboo fiber, cotton fiber, viscose fiber and tencel as representatives;
[0043] Ordinary fiber: This application mainly adopts one or more of bamboo fiber, cotton fiber, wood fiber, hemp fiber, regenerated cellulose fiber, polylactic acid fiber, polyvinyl alcohol fiber, polyethylene fiber, polyamide fiber, polyester, acrylic fiber, polypropylene fiber and ES fiber. This application takes bamboo fiber and polyester as representatives;
[0044] Alkalizing agent: including sodium hydroxide, potassium hydroxide, etc., this application only uses sodium hydroxide as an example, and specifically uses a commercially available sodium hydroxide product with a CAS number of 1310-73-2;
[0045] Etherifying agent: including chloroacetic acid, sodium chloroacetate, propylene oxide, etc., this application only uses chloroacetic acid as an example, and specifically uses a commercially available chloroacetic acid product with a CAS number of 79-11-8;
[0046] Alcohol: This application uses commercially available products of methanol, ethanol, and isopropanol as representatives;
[0047] Acid: This application uses commercially available products of acetic acid, citric acid, hydrochloric acid, and nitric acid as representatives;
[0048] Ammonia: Homemade.
[0049] The present application is further described in detail below in conjunction with the accompanying drawings, embodiments and comparative examples.
[0050] Example 1
[0051] The method for preparing the modified fiber fabric comprises the following steps:
[0052] Raw material processing: Take bamboo pieces with an absolute dry weight of 10kg and cut them into pieces of 30-40cm in length and 2-3cm in width, soak them in distilled water for 12 hours, put them in a cooker, and use the sulfate method to make pulp. The cooking process is as follows: use 20% alkali (in terms of NaOH), 20% sulfidation (in terms of Na2S), 1:4 material-liquid ratio, gradually heat to 170°C for 2 hours, and then continue to keep warm for 2 hours. After the cooking is completed, wash the obtained bamboo pulp with distilled water, filter it with a flat screen with a sieve gap of 0.15mm, remove impurities, and dry the water to obtain bamboo fiber;
[0053] Preparation of CMC-H: 1 kg of bamboo fiber is taken, and alkalized and etherified under the premise of maintaining the fiber morphology of the fiber, that is, firstly added into a 30 wt% sodium hydroxide solution for reaction, alkalized at 65°C for 1 hour, and alkalized cellulose fiber is obtained; then 0.8 kg of etherification liquid is added into the alkalized cellulose fiber for etherification, and the specific components of the etherification liquid are 45 wt% of chloroacetic acid, 35 wt% of ethanol and 20 wt% of distilled water, and etherified at 65°C for 2.5 hours to obtain etherified cellulose;
[0054] Then, an acid solution is added and mixed evenly, wherein the acid solution is composed of 35% acetic acid and 65% pure water by volume, the amount of the acid solution added is 100 kg, and the acid solution is added twice, 50 kg each time, and the acid solution is stirred and acidified for 0.5 h after the first addition of the acid solution, and the acid solution is added for the second time after draining, and the acid solution is stirred and acidified for 0.5 h after the addition of the acid solution, to obtain carboxymethyl cellulose CMC-H;
[0055] Washing: Wash CMC-H with pure water until the pH of the washing residue is ≥4, and then obtain washed fiber;
[0056] Papermaking: Put the washed fiber into the water dispersion and stir to disperse it evenly. 1.0wt% of the dispersion system is used for papermaking. The paper thickness is 15g / m 2 , obtaining a primary film;
[0057] Ammoniation: Roll the initial sheet into a roll with a diameter of 15 cm, place it in a sealed container, introduce ammonia at a temperature of 25±5°C, adjust the pressure at 200-300 kPa for ammoniation, and the reaction time is 2 hours;
[0058] Drying and removal of unbound ammonia: Place the ammonium-treated primary sheet in a drying oven at 65°C for 6 minutes to heat and dry until the moisture content reaches 10%. This will give the ammonium-treated fiber sheet - carboxymethyl cellulose ammonium absorbent material. For photos of the actual product, see Figure 1 .
[0059] Example 2
[0060] The method for preparing the modified fiber fabric comprises the following steps:
[0061] Preparation of CMC-H: 1 kg of commercially available viscose fiber with a fiber length of 3.8 cm is taken, and alkalized and etherified while maintaining the fiber morphology, that is, firstly added to a 27 wt% sodium hydroxide solution for reaction, alkalized at 65°C for 0.8 h, and alkalized cellulose fiber is obtained; then 0.8 kg of etherification liquid is added to the alkalized cellulose fiber for etherification, the specific components of the etherification liquid are 45 wt% chloroacetic acid, 35 wt% ethanol and 20 wt% distilled water, and etherified at 65°C for 2.0 h to obtain etherified cellulose; then acid solution is added and mixed evenly, wherein the acid solution is composed of 30% citric acid and 70% pure water by volume percentage, the amount of acid solution added is 100 kg, and the acid solution is added twice, 50 kg each time, and the acid solution is stirred and acidified for 0.5 h after the first addition of the acid solution, and after draining, the acid solution is added for the second time, and the acid solution is continued to be stirred and acidified for 0.5 h after the acid solution is added to obtain CMC-H;
[0062] Washing: Wash CMC-H with pure water until the pH of the washing residue is ≥4, and then obtain washed fiber;
[0063] Nonwoven: The washed fibers are laid straight or cross-laid, and the fiber web is punctured with high-pressure water to entangle the fibers into a cloth, which is dried to form a 45g / m 2 The spunlace fabric is initially formed into sheets;
[0064] Ammoniation: Roll the initial sheet into a roll with a diameter of 10 cm, place it in a sealed container, introduce ammonia at a temperature of 65±5°C, adjust the pressure at 600-700 kPa for ammoniation, and the reaction time is 45 minutes;
[0065] Drying and removing unbound ammonia: Place the ammonium-treated primary sheet in a drying oven at 65°C and heat dry for 6 minutes until the moisture content is 15%, thereby obtaining the ammonium-treated fiber sheet - ammonium carboxymethyl cellulose absorbent material.
[0066] Example 3
[0067] The method for preparing the modified fiber fabric comprises the following steps:
[0068] Preparation of CMC-H: 1 kg of commercially available cotton fiber with a fiber length of 0.3-1.5 cm is taken, and alkalization and etherification are performed while maintaining the fiber morphology, that is, firstly added to a 27 wt% sodium hydroxide solution for reaction, and alkalization reaction is performed at 65°C for 0.8 h to obtain alkalized cellulose fiber; then 0.8 kg of etherification liquid is added to the alkalized cellulose fiber for etherification, wherein the specific components of the etherification liquid are 45 wt% chloroacetic acid, 35 wt% ethanol and 20 wt% distilled water, and etherification is performed at 65°C for 2.0 h to obtain etherified cellulose; then acid solution is added and mixed evenly, wherein the acid solution is composed of 60% acetic acid and 40% pure water by volume percentage, the amount of acid solution added is 100 kg, and the acid solution is added twice, 50 kg each time, and after the first addition of the acid solution, the acid solution is stirred and acidified for 0.5 h, and then the second acid solution is added, and after the acid solution is added, the acid solution is continuously stirred and acidified for 0.5 h to obtain CMC-H;
[0069] Washing: Wash CMC-H with pure water until the pH of the washing residue is ≥4, and then obtain washed fiber;
[0070] Papermaking: Put the washed fiber into the water dispersion and stir to disperse it evenly. 1.5wt% of the total weight of the dispersion system is used for papermaking. The papermaking thickness is 30g / m 2 , obtaining a primary film;
[0071] Ammoniation: Roll the initial sheet into a cloth roll with a diameter of 12 cm, place it in a sealed container, introduce ammonia gas at a temperature of 125±5°C, adjust the pressure at 1400-1500 kPa for ammoniation, and the reaction time is 30 minutes;
[0072] Drying and removing unbound ammonia: The ammonium-treated primary sheet is placed in a drying oven at 65°C and heated and dried for 6 minutes until the moisture content is 12%, thereby obtaining the ammonium-treated fiber sheet - ammonium carboxymethyl cellulose absorbent material.
[0073] Example 4
[0074] The method for preparing the modified fiber fabric comprises the following steps:
[0075] Preparation of CMC-H: 1 kg of commercially available Tencel fiber with a single fiber fineness of 3.0 dtex and a fiber length of 0.5-0.8 cm is taken, and alkalization and etherification are performed while maintaining the fiber morphology, that is, firstly added to a 28 wt% sodium hydroxide solution for reaction, and alkalization reaction is performed at 65°C for 1.2 hours to obtain alkalized cellulose fiber; then 0.7 kg of etherification liquid is added to the alkalized cellulose fiber for etherification, and the specific components of the etherification liquid are 45 wt% chloroacetic acid, 35 wt% ethanol and 20 wt% distilled water, and etherification is performed at 65°C for 1.2 hours to obtain etherified cellulose; then acid solution is added and mixed evenly, wherein the acid solution is composed of 37% acetic acid, 3% hydrochloric acid and 60% pure water by volume percentage, and the amount of acid solution added is 100 kg, and the acid solution is added twice, 50 kg each time, and after the first addition of the acid solution, the acid solution is stirred and acidified for 0.5 hours, and then the second acid solution is added, and the acid solution is continued to be stirred and acidified for 0.5 hours after the acid solution is added, and CMC-H is obtained;
[0076] Washing: Wash CMC-H with pure water until the pH of the washing residue is ≥4, and then obtain washed fiber;
[0077] Papermaking: The washed fibers are put into the water dispersion and stirred to disperse evenly. 1.2wt% of the dispersion system is used for papermaking. The paper thickness is 20g / m 2 , obtaining a primary film;
[0078] Ammoniation: Roll the initial sheet into a roll with a diameter of 15 cm, place it in a sealed container, introduce ammonia at a temperature of 25±5°C, adjust the pressure at 200-300 kPa for ammoniation, and the reaction time is 2 hours;
[0079] Drying and removing unbound ammonia: The ammonium-treated primary sheet is placed in a drying oven at 65°C and heated and dried for 6 minutes until the moisture content reaches 11%, thereby obtaining the ammonium-treated fiber sheet - ammonium carboxymethyl cellulose absorbent material.
[0080] Example 5-Example 6
[0081] Example 5 and Example 6 are based on the method of Example 1, and the difference is that the acidification concentration in the step of preparing CMC-H is adjusted. In Example 5, the acetic acid concentration is lowered to 28%, and the proportion of pure water is increased to 72%; in Example 6, the acetic acid concentration is lowered to 16%, and the proportion of pure water is increased to 84%.
[0082] Example 7
[0083] Example 7 is based on the method of Example 1, except that the acidification time in the step of preparing CMC-H is adjusted. In Example 7, the acidification time is 0.4 h.
[0084] Example 8-Example 9
[0085] Example 8-Example 9 is based on the method of Example 1, but the difference is that the ammoniated ammonia gas is changed into an ammonia solution for soaking. In which, Example 8 is 33% ammonia water; Example 9 is 10% ammonium chloride aqueous solution.
[0086] Example 10-Example 11
[0087] Example 10-Example 11 is based on the method of Example 1, except that, in the papermaking process, the washed fiber is put into the ordinary fiber-water dispersion and stirred and dispersed evenly, wherein the ordinary fiber of Example 10 is the wood fiber prepared from the above raw material; the ordinary fiber of Example 11 is the hemp fiber prepared from the above raw material; and the weight ratio of the washed fiber and the ordinary fiber is controlled to be 50:50, and the weight sum of the washed fiber and the ordinary fiber is 1.0wt% of the dispersion system for papermaking, and the papermaking thickness is 15g / m 2 , and obtain the initial film.
[0088] Example 12-Example 13
[0089] Example 12-Example 13 is based on the method of Example 2, except that in the non-woven process, the washed fibers and ordinary fibers are mixed and combed in a ratio of 50:50. Among them, the ordinary fibers of Example 12 are regenerated cellulose fibers prepared from the above raw materials; the ordinary fibers of Example 13 are ES fibers prepared from the above raw materials; and the combed fibers are laid straight or cross-overlapped, and the fiber web is punctured with high-pressure water to entangle the fibers into a cloth, which forms a 45g / m 2 The spunlace fabric is initially formed into sheets.
[0090] Comparative Example 1
[0091] The method for preparing the modified fiber fabric comprises the following steps:
[0092] 1kg of bamboo fiber powder passing through a 60-mesh screen is alkalized and etherified, that is, first added to a 30wt% sodium hydroxide solution for reaction, alkalized at 65°C for 1h, and alkalized cellulose fibers are obtained; then 0.8kg of etherified liquid is added to the alkalized cellulose fibers for etherification, the specific components of the etherified liquid are 45wt% acetic acid and 55wt% distilled water, and etherified at 65°C for 2.5h to obtain etherified cellulose; then acid solution is added and mixed evenly, wherein the acid solution is composed of 35% acetic acid, 30% ethanol and 35% pure water by volume percentage, the amount of acid solution added is 100kg, and the acid solution is added twice, 50kg each time, and the acid solution is added for the first time after stirring and acidifying for 0.5h, and then the second acid solution is added, and the acidification is continued for 0.5h after the acid solution is added. During the acidification process, the bamboo fiber powder is difficult to maintain the fiber form and dissolves, and the subsequent washing, papermaking, ammoniation and drying processes cannot be carried out. It can be seen that the modified fiber fabric ammonium carboxymethyl cellulose water-absorbing material of the present invention requires raw materials based on fiber form to be prepared.
[0093] Performance testing
[0094] The water-absorbing materials prepared in Examples 1 to 13 and Comparative Example 1 were subjected to the following performance tests, and the blank group was the raw material viscose fiber of Example 2. The test results are shown in Table 2.
[0095] 1. Degree of substitution
[0096] The degree of substitution of the etherified cellulose in Examples 1-13 was determined according to GB 1886.232-2016.
[0097] 2. Water absorption and water retention
[0098] The water-absorbing material prepared in Examples 1-17 was cut into samples with a diameter of 10 cm. The mass m1 (g) of the sample before immersion was weighed first, and then the sample was soaked in deionized water. After 12 hours, it was taken out and fully drained and weighed. The mass m2 (g) was then weighed. The sample that had fully absorbed water was placed in an oven at 65° C. for drying, and the drying time (h) required for the weight of the sample to be recovered to m1 (g) was recorded. The water absorption rate of the water-absorbing material was simultaneously calculated as [(m2-m1) / m1]*100%, wherein the higher the water absorption rate, the better the water absorption, and the longer the drying time, the better the water retention.
[0099] 3. Fiber mechanical strength and flexibility
[0100] According to GB / T14337-2022, the dry breaking strength, wet breaking strength and elongation at break of the fiber raw materials in the absorbent material are measured. The larger the dry breaking strength, wet breaking strength and elongation at break, the better. The dry breaking strength and wet breaking strength represent mechanical strength, and the elongation at break represents flexibility.
[0101] 4. Sheet tensile strength test
[0102] According to GB / T12914-2008, the test piece was cut into 100mmx100mm, unit: m / N.
[0103] 5. Determination of breaking strength of nonwoven sheets
[0104] Tested according to textile standard FZ / T 60005 method.
[0105] 6. Determination method of -CH2COONH4 content
[0106] The w(-CH2COONH4) content is calculated according to the following formula:
[0107] w(-CH2COONH4)=N%*76 / 14*100%, wherein N% is the nitrogen content in the ammonium carboxymethyl cellulose product determined by an elemental analyzer, Kjeldahl method or Kjeldahl method.
[0108] Table 2 Performance test table of Examples 1-13 and Comparative Example 1
[0109]
[0110]
[0111] Combined with Table 2, it can be obtained that: Example 1, the raw material is cellulose raw bamboo cellulose, after implementing the method and process of the present invention, the modified fiber fabric carboxymethyl cellulose ammonium absorbent material product has a degree of substitution of 0.4, a water absorption rate of 176 times its own weight, and excellent water absorption performance; the sheet tensile strength is 230N / m, and the fiber still maintains excellent physical properties after the treatment.
[0112] In Example 2, the raw material is viscose fiber of regenerated cellulose fiber. After implementing the method and process of the present invention, the degree of substitution of the obtained product is 0.33. Due to the new structure of the regenerated cellulose fiber skin, the degree of substitution is slightly lower than that of Example 1; its water absorption rate is 201 times its own weight, and the water absorption performance is excellent; the fiber dry breaking strength is 2.1cN / dtex, and the fiber breaking elongation is 22%. Compared with the blank group control, the fiber dry breaking strength after the treatment is not significantly reduced, indicating that the raw material fiber has not been degraded during the preparation method of the present invention. The breaking strength of the non-woven sheet is 165N, and the strength of the non-woven fabric is good.
[0113] Example 3, the raw material is cotton fiber. After implementing the method and process of the present invention, the degree of substitution of the obtained product is 0.55; the water absorption rate reaches 170 times of its own weight, and the water absorption performance is excellent; the sheet tensile strength is 310N / m, and the excellent physical properties of the fiber raw material are still maintained.
[0114] Example 4, Tencel fiber, whose raw material is regenerated cellulose fiber, after implementing the method and process of the present invention, the degree of substitution of the obtained product is 0.22. Due to the new structure of the regenerated cellulose fiber skin, the degree of substitution is slightly lower than that of Example 1; the water absorption rate is 217 times its own weight, and the water absorption performance is excellent. The fiber dry breaking strength is 4.97cN / dtex, and the fiber breaking elongation is 18%. Compared with viscose fiber, Tencel fiber has better physical properties than raw material fiber, and the fiber wet breaking strength is 1.9cN / dtex. The breaking strength of the non-woven sheet is 115N. Because the surface of Tencel fiber is smooth, the breaking strength of the cloth is lower than that of viscose fiber cloth.
[0115] In summary, the performance test results of the carboxymethyl cellulose ammonium water-absorbing material prepared by the above-mentioned embodiments 1 to 4 of the present invention can be obtained. The modified fiber fabric prepared by the method for preparing the modified fiber fabric of the present invention, the modified fiber fabric carboxymethyl cellulose ammonium water-absorbing material obtained, has little effect on the original physical properties of the original fiber. On the basis of maintaining the excellent physical properties of the raw fiber, it also has excellent water absorption, water retention and biodegradability due to the special groups brought by the carboxymethyl cellulose ammonium. It also has excellent biocompatibility because of its own structure without potential cytotoxicity, and can be well applied to the fields of health care, medical treatment, industry, agriculture and forestry. The relationship between the water absorption rate of the carboxymethyl cellulose ammonium water-absorbing material prepared by the present invention and -COONH4, through the process of the present invention, cellulose has three groups at C2, C3, and C6, namely -OH, -COOH and -COONH4. First, from the perspective of the interaction between water molecules and hydrophilic groups, similar dissolves, and according to the polarity of the group, the order of interaction with water molecules from strong to weak is -COONH4, -COOH, OH. Therefore, -COONH4 has better hydrophilicity and the water absorption performance of the -COONH4 group is significantly better than that of the -COOH and -OH groups.
[0116] On the other hand, the -COONH4 group is an ionic group and will ionize into -COO- and NH4 in aqueous solution. + ions. -COO- is fixed on the cellulose chain, while NH4 + But they can move freely, precisely because of NH4 + The presence of ions causes the difference in osmotic pressure. When the material comes into contact with water, the microscopic cellulose fiber bundles expand, and NH4 + Ionization creates a difference in ion concentration inside and outside the cellulose mesh, which causes water molecules to penetrate into the cellulose mesh structure under osmotic pressure. Therefore, the higher the content of -COONH4 groups, the more water molecules penetrate into the cellulose. However, -OH and -COOH do not have ion osmotic pressure, so their water absorption rate is not as good as that of -COONH4 groups.
[0117] Based on the hydrogen bonds formed by water molecules and oxygen atoms with strong electronegativity in the material, H shows +1 valence; N shows -3 valence, so the electronegativity of the O atom in -COONH4 is stronger than that of -OH and -COOH hydrogen. When the -COONH4 content is high, free water forms hydrogen bonds with O and is imprisoned, forming frozen water, and then forming a gel state with good water retention. Therefore, the terminal modified groups at carbon positions C6, C2, and C3 in the carboxymethyl cellulose ammonium molecule in the carboxymethyl cellulose ammonium water-absorbing material of the present invention include -CH2COONH4, and the content range thereof is limited to 4.3%-58.9%, and -CH2COONH4 is directly connected to the glucose unit of the fiber, which can achieve the high water absorption performance of the present invention.
[0118] The preparation method of the present invention uses cellulose fiber as raw material, which is applicable to natural cellulose fiber and / or regenerated cellulose fiber. The acid concentration in the acidification process is strictly controlled, and then ammoniation is performed with ammonia at a temperature of 0-130°C and a pressure of 102kPa to less than the liquefied vapor pressure of ammonia at the corresponding temperature. Afterwards, the cellulose is dried and the unbound ammonia is removed, thereby keeping the cellulose in a fiber form, ensuring the physical properties of the product fiber, and further ensuring the softness and physical properties of the corresponding product paper or non-woven fabric. While maintaining the smooth progress of the reaction, the addition of organic solvents and impurities such as sodium ions and potassium ions can be omitted, thereby improving the preparation efficiency and product purity of the modified fiber fabric carboxymethyl cellulose ammonium absorbent material.
[0119] The results of Example 5 and Example 6 show that when the acid concentration used in the acidification method of the present invention is lower than 29%, the water content is too high, resulting in a large amount of swelling or dissolution of the fiber during acidification. Because the fiber in Example 5 and Example 6 swells or dissolves a lot, it cannot be tested.
[0120] From the performance test results of the product in Example 7, it can be seen that compared with Example 1, the basic method and parameters are the same, the difference is that the acidification time is shortened, and the water absorption rate is reduced due to the shortened acidification time, which is 119 times its own weight, and the tensile strength of the sheet is 90N / m.
[0121] The product performance test results in Examples 8 and 9 are the same as those in Example 1, with the basic methods and parameters being the same, except that an ammonia solution is selected for the ammonia treatment. Since the acidified fibers are dissolved in the ammonia solution, the fibers swell or dissolve in large quantities and cannot be tested.
[0122] The preparation methods of Example 10 and Example 11 are based on the method of Example 1, except that in the papermaking process, the washed fiber is put into the ordinary fiber-water dispersion and stirred and dispersed evenly, wherein the ordinary fiber added in Example 10 is wood fiber; and the hemp fiber added in Example 11; and the weight ratio of the washed fiber to the ordinary fiber is controlled to be 50:50. It is measured that the water absorption rate is 67 times and 77 times of its own weight respectively; the tensile strength of the papermaking sheet is enhanced due to the addition of ordinary fiber, which is 260N / m and 330N / m respectively.
[0123] Examples 12 to 13 are based on the preparation method of Example 2, except that the washed fibers and ordinary fibers are mixed and combed in a ratio of 50:50 in the nonwoven process. It was measured that the water absorption rates were 114 times and 121 times of their own weight, respectively, and the breaking strengths of the nonwoven sheets were 209N and 480N, respectively. The ordinary fibers of Example 13 were ES fibers, and due to the performance of ES fibers, the breaking strength of the nonwoven sheets was greatly enhanced.
[0124] Application Examples
[0125] The modified fiber fabric absorbent materials obtained in Examples 1 to 4 of the present invention have excellent water absorption, water retention, biodegradability, and excellent biocompatibility, so they can be well used in health care, medical care, industry, agriculture and forestry and other fields. Specifically, they can be made into absorbent pads, absorbent papers, absorbent strips, etc., and further used in including but not limited to sanitary napkins, wound dressings, facial masks, etc.
[0126] The above are only embodiments of the present invention. For example, cellulose fibers can be natural cellulose fibers such as cotton, hemp, bamboo, straw, etc., or regenerated cellulose fibers such as viscose, tencel, cuprammonium, modal, etc., or mixed fibers of the above two types of fibers; ordinary fibers are one or more of bamboo fibers, cotton fibers, wood fibers, hemp fibers, regenerated cellulose fibers, polylactic acid fibers, polyvinyl alcohol fibers, polyethylene fibers, polyamide fibers, polyester, acrylic, polypropylene fibers and ES fibers; acids are biocompatible acids, and specific acids are one or more of acetic acid, citric acid, hydrochloric acid, nitric acid, and formic acid. The washed fibers of the present invention can be used to prepare pure carboxymethyl cellulose ammonium fiber sheets as needed, and can also be used in combination with other ordinary fibers to make composite fiber sheets, both of which can realize the modified fiber fabrics and preparation methods of the present invention.
[0127] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A modified fiber fabric, characterized in that: The fiber fabric raw material is based on maintaining the fiber shape, and is sequentially modified to carboxymethyl cellulose and ammoniumized with ammonia to obtain a fiber fabric of carboxymethyl cellulose ammonium. The fiber fabric raw material is subjected to a modification treatment reaction in order to maintain its fiber shape. Specifically, during the modification treatment reaction, in the fiber molecules of the fiber fabric raw material, the 1,4-glycosidic bonds (i.e., the connection between C1 and C4) in the glucose molecules connected to form parallel cellulose chains remain unchanged, and a modification reaction is performed on specific chemical groups occupying specific carbon positions C6, C2, and C3 on the molecular chains of the fibers.
2. The modified fiber fabric according to claim 1, characterized in that: The ammonia ammoniation treatment is performed until the degree of substitution in the fiber fabric of the ammonium carboxymethyl cellulose is 0.2-3.0, the terminal modification groups of the specific chemical groups at the carbon positions C6, C2, and C3 in the ammonium carboxymethyl cellulose molecules include -CH2COONH4, and the content range of -CH2COONH4 is limited to 4.3%-58.9%, and -CH2COONH4 is directly connected to the glucose unit of the fiber, and the breaking strength of the fiber in the fiber fabric of the ammonium carboxymethyl cellulose is not less than 60% of the breaking strength of the fiber in the fiber fabric raw material.
3. The modified fiber fabric according to claim 2, characterized in that: The fiber fabric raw material is cellulose fiber, and the cellulose fiber is natural cellulose fiber and / or regenerated cellulose fiber; the length of the cellulose fiber is not less than 0.5 mm.
4. A modified fiber fabric according to claim 1 or claim 3, characterized in that: In the modification process to carboxymethyl cellulose, alkalization and etherification are sequentially performed based on maintaining the fiber shape of the cellulose fibers, and then an acid solution is added and mixed evenly. The volume percentage concentration of the acid in the acid solution is ≥29%, and the modified product obtained after the acidification reaction is carboxymethyl cellulose CMC-H.
5. A method for preparing a modified fiber fabric, characterized in that: The fiber fabric raw material is based on maintaining the fiber shape, and is sequentially modified to carboxymethyl cellulose and ammoniumized with ammonia to obtain a fiber fabric of carboxymethyl cellulose ammonium. The fiber fabric raw material is subjected to a modification treatment reaction in order to maintain its fiber shape. Specifically, during the modification treatment reaction, in the fiber molecules of the fiber fabric raw material, the 1,4-glycosidic bonds (i.e., the connection between C1 and C4) in the glucose molecules connected to form parallel cellulose chains remain unchanged, and a modification reaction is performed on specific chemical groups occupying specific carbon positions C6, C2, and C3 on the molecular chains of the fibers.
6. The method for preparing a modified fiber fabric according to claim 5, characterized in that: The fiber fabric raw material is cellulose fiber, and the length of the cellulose fiber is not less than 0.5 mm; In the modification process of carboxymethyl cellulose, alkalization and etherification are sequentially performed based on maintaining the fiber shape, and then acid solution is added and mixed evenly; the volume percentage concentration of the acid in the acid solution is ≥29%, and the modified product obtained after the acidification reaction is carboxymethyl cellulose CMC-H; After washing, washed fiber is obtained; The washed fiber is then treated with ammonia gas to obtain a fiber fabric whose modified product is ammonium carboxymethyl cellulose. The ammonia ammoniation treatment is performed until the degree of substitution in the fiber fabric of the ammonium carboxymethyl cellulose is 0.2-3.0, the terminal modification groups of the specific chemical groups at the carbon positions C6, C2, and C3 in the ammonium carboxymethyl cellulose molecules include -CH2COONH4, and the content range of -CH2COONH4 is limited to 4.3%-58.9%, and -CH2COONH4 is directly connected to the glucose unit of the fiber, and the breaking strength of the fiber in the fiber fabric of the ammonium carboxymethyl cellulose is not less than 60% of the breaking strength of the fiber in the fiber fabric raw material.
7. The method for preparing a modified fiber fabric according to claim 6, characterized in that: After washing with water until the pH of the washing residue is ≥4.0, washed fiber is obtained.
8. The method for preparing a modified fiber fabric according to claim 6, characterized in that: The post-treatment drying step in the step of ammoniation with ammonia is heating and drying, heating and drying the ammonized fiber fabric, and the heat obtained simultaneously removes the uncombined ammonia in the reaction, and heating and drying until the moisture content of the fiber fabric of the carboxymethyl cellulose ammonium is ≤15%.
9. The method for preparing a modified fiber fabric according to claim 6, characterized in that: In the step of ammoniation with ammonia, tableting is first performed and then the ammoniation step is performed, specifically: The washed fibers are firstly made into a primary sheet by a papermaking or non-woven process, and then the primary sheet is ammonized with ammonia to obtain an ammonized fiber sheet.
10. The method for preparing a modified fiber fabric according to claim 9, characterized in that: In the process of preparing the washed fiber into a primary sheet, When papermaking is adopted, in the papermaking step, the washed fiber is firstly put into pure water or ordinary fiber-water dispersion liquid and dispersed evenly, and then papermaking is carried out, and the weight ratio of the washed fiber to the ordinary fiber is 10-100:90-0; When the non-woven process is adopted to prepare the sheet, in the non-woven step, the washed fiber is first mixed with the common fiber and then the non-woven sheet is prepared, and the weight ratio of the washed fiber to the common fiber is 10-100:90-0.
11. The method for preparing a modified fiber fabric according to claim 10, characterized in that: The common fiber is one or more of bamboo fiber, cotton fiber, wood fiber, hemp fiber, regenerated cellulose fiber, polylactic acid fiber, polyvinyl alcohol fiber, polyethylene fiber, polyamide fiber, polyester, acrylic, polypropylene and ES fiber.
12. The method for preparing a modified fiber fabric according to claim 8, characterized in that: In the step of ammoniation with ammonia, the ammoniation treatment is first performed and then the tableting step is performed, specifically: The washed fiber is firstly dried, and then the washed fiber is ammoniumized with ammonia to generate CMC-NH4 fiber, and then the unbound ammonia is removed by heating the air duct, and the obtained fiber dry material is evenly spread and needle-punched to obtain an ammoniumized fiber sheet.
13. The method for preparing a modified fiber fabric according to claim 6, characterized in that: The acid is a biocompatible acid, and specifically is one or more of acetic acid, citric acid, hydrochloric acid, nitric acid, and formic acid.
14. The method for preparing a modified fiber fabric according to claim 6, characterized in that: The acidification is performed multiple times until the fiber acidification reaction is sufficient, and the total acidification time is 0.8h-1.5h.
15. The method for preparing a modified fiber fabric according to claim 13, characterized in that: The acid solution also contains alcohol with a volume percentage concentration of 0-50%; the alcohol is one or more of methanol, ethanol, and isopropanol.
16. The method for preparing a modified fiber fabric according to claim 6, characterized in that: The ammonia gas is obtained by evaporating liquid ammonia, ammonia water or ammonia-alcohol water at a temperature of 0-130° C. and a pressure of 102 kPa to a pressure lower than the liquefied vapor pressure of ammonia gas at the corresponding temperature.
Citation Information
Patent Citations
Preparation method of ammonium carboxymethylcellulose
CN102558366A
Preparation method of high-viscosity ammonium carboxymethyl cellulose
CN112321730A
Method for preparing high-substitution degree ammonium carboxymethyl cellulose by means of mixed strong acid
CN103242454A
Preparation method for golden cotton fiber / cotton fiber fabric with silver texture
CN103820993A
Preparation method of carboxymethyl cellulose cotton
CN105461813A
